Synthesis, Molecular Docking, and Biofilm Formation Inhibitory Activity of Bis(Indolyl)Pyridines Analogues of the Marine Alkaloid Nortopsentin - Heba M. Abo-Salem; Hayam A. Abd El Salam; Anhar Abdel-Aziem; Mohamed S. Abdel-Aziz; Eslam Reda El-Sawy (Molecules, 2021)
An efficient and simple protocol for the synthesis of a new class of diverse bis(indolyl)pyridines analogues of the marine alkaloid nortopsentin has been reported. A one-pot four-component condensation of 3-cyanocarbomethylindole, various aldehyde, 3-acetylindole, and ammonium acetate in glacial acetic acid led to the formation of 2,6-bis(1H-indol-3-yl)-4-(substituted-phenyl)pyridine-5-carbonitriles. Additionally, 2,6-bis(1H-indol-3-yl)-4-(benzofuran) pyridine-5-carbonitriles were prepared via a one-pot four-component condensation of 3-cyanocarbomethylindole, various N-substituted-indole-3-aldehydes, 2-acetylbenzofuran, and ammonium acetate. The synthesized compounds were evaluated for their ability to inhibit biofilm formation against the Gram-positive bacterial reference strains Staphylococcus aureus ATCC 6538 and the Gram-negative strain Escherichia coli ATCC 25922. Some of the new compounds showed a marked selectivity against the Gram-positive and Gram-negative strains. Remarkably, five compounds 4b, 7a, 7c, 7d and 8e demonstrated good antibiofilm formation against S. aureus and E. coli. On the other hand, the release of reducing sugars and proteins from the treated bacterial strains over the untreated strains was considered to explain the disruption effect of the selected compound on the contact cells of S. aureus and E. coli. Out of all studied compounds, the binding energies and binding mode of bis-indole derivatives 7c and 7d were theoretically the best thymidylate kinase, DNA gyrase B and DNA topoisomerase IV subunit B inhibitors.